Leading reasons for antibiotic prescriptions in pediatric respiratory infections: influence of fever in a primary care setting - Marina Picca; Romeo Carrozzo; Gregorio Paolo Milani; Antonio Corsello; Marina Macchi; Roberto Buzzetti; Paola Marchisio; Chiara Mameli (BMC, 2023)
Abstract Background Antibiotic overuse in children is a significant public health concern, as it can lead to the emergence and spread of antibiotic-resistant bacteria. Although respiratory infections account for most antibiotic prescriptions in children, many of these infections are viral and do not require antibiotics. In this study, we aimed to investigate the use of antibiotics in children with respiratory infections in a primary care setting and to explore the possible role of fever on antibiotic prescription. Methods We conducted a prospective observational study that evaluated preschool children aged 0-5 years who were assessed by their primary care pediatricians for respiratory infectious diseases between October 2019 and March 2021. The study involved 69 public primary care pediatricians and a total of 678 pediatric episodes for respiratory infections. Results Amoxicillin/clavulanate was the most frequently prescribed drug. Bronchitis accounted for most of inappropriate antibiotic prescriptions (73%). Furthermore, the presence of fever was associated with a ~ 300% increase in the likelihood of prescribing antibiotics for respiratory infections that do not typically require antibiotics. Conclusion Our findings emphasize the need for adherence to international guidelines and recommendations in the primary care of children to reduce unnecessary antibiotic use and prevent the development of antibiotic resistance. This study also underscores the potential relevance of new studies to evaluate antibiotic prescription attitudes in other clinical settings and geographical areas.